Association Between Cardiometabolic Index and Mortality Among Patients with Atherosclerotic Cardiovascular Disease: Evidence from NHANES 1999–2018 - Duo Yang; Wei Li; Wei Luo; Yunxiao Yang; Jiayi Yi; Chen Li; Hai Gao; Xuedong Zhao (Medicina)
Background and Objectives: Atherosclerotic cardiovascular disease (ASCVD) remains a leading cause of global morbidity and mortality. The cardiometabolic index (CMI) has been shown to be associated with metabolic disorders and mortality in general populations, but its role in ASCVD-specific mortality risk remains unexplored. Materials and Methods: This cohort study was based on the National Health and Nutrition Examination Survey (NHANES). Weighted Cox proportional hazards models were fitted to estimate the associations between CMI and mortality. Restricted cubic splines were used to explore nonlinear relationships. Subgroup analyses were used to investigate potential differences among specific ASCVD patients. Results: A total of 2157 patients with ASCVD were included. Over a median 83-month follow-up, 887 all-cause and 300 cardiovascular deaths occurred. Each unit increase in CMI was associated with an 11.3% increased risk of all-cause mortality (HR = 1.113, 95% CI: 1.112–1.115) and a 6.4% increased risk of cardiovascular mortality (HR = 1.064, 95% CI: 1.062–1.065). There was a nonlinear J-shaped relationship between CMI and all-cause mortality, while the risk of cardiovascular mortality increased linearly with increasing CMI. Conclusions: These findings underscore the importance of monitoring and managing CMI in patients with ASCVD in clinical practice and suggest that optimizing CMI levels may help reduce the risk of death and improve the long-term prognosis of patients.